Botanical control of citrus green mold and peach brown rot on fruits assays using a persicaria acuminata phytochemically characterized extract - Di Liberto, Melina Gabriela (2021)
Persicaria acuminata (Polygonaceae) is a perennial herb that grows in the central area of Argentina and it is commonly used by native populations to heal infected wounds and other conditions related to fungal infections. In this article, we explored the in vitro antifungal activity of its ethyl acetate extract against a panel of three fruit phytopathogenic fungi including: Penicillium digitatum, P. italicum, and Monilinia fructicola. The sesquiterpenes isolated from the extract were also evaluated against these strains, demonstrating that the dialdehyde polygodial was the responsible for this activity. In order to encourage the use of the extract rather than the pure compound, we displayed ex vivo assays using fresh oranges and peaches inoculated with P. digitatum and M. fructicola, respectively, and subsequently treated by immersion with an extract solution of 250 and 62.5 µg/mL, respectively. There were no statistically significant differences between the treatments with commercial fungicides and the extract over the control of both fruit rots. The concentration of the active compound present in the extract used on fruit experiments was determined by Gas Chromatography-Mass Spectroscopy. Finally, cytotoxicity evaluation against Huh7 cells showed that P. acuminata extract was less cytotoxic than the commercial fungicides at the assayed concentrations. After these findings we could conclude that a chemically characterized extract of P. acuminata should be further developed to treat fungal diseases in fruits from an agro-ecological model.